ANALISIS FAKTOR – FAKTOR GOOD CORPORATE GOVERNANCE TERHADAP KONSERVATISME AKUNTANSI (STUDI PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Adhriatik, Nenny; Ismangil, Ismangil (Liability, 2019)
This research aims to examine the influence of good corporate governance to conservatism level. Accounting conservatism level is a dependent variable in this research and good corporate governance as independent variable that was applied in this research are independency of boards, size of boards, institutional ownership, managerial ownership and audit committee. The samples of this research are the consumer good firms as sub sector of manufacturing firms listed in Indonesian Stock Exchange in 2011 -2013. The samples are collected using purposive sampling method and resulted 34 firms become the samples. Hyphotesys testing using multiple regression. The result of this research show that independency of boards, institutional ownership, managerial ownership and audit committee have not effect significantly to application of conservatism on accounting. Whereas, for size of boards to application of conservatism on accounting have effect significantly. The application of conservatism on accounting in the financial statement still raises the pro and con. However, this research is more lead to pro opinion because it can minimize the manager?s oppotunistic behavior on reporting their profit.